Formation of professionalism of the teacher in terms of inclusive education - Svitlana Chupakhina (Vasyl Stefanyk Precarpathian National University, 2017)
In the article the problem of formation of future teacher professionalism in terms ofinclusive education. Updated theoretical and methodological principles and problems raisedreasonably practical orientation of theoretical knowledge and practical skills of organizationof correctional and educational work with children of preschool and primary school age interms of inclusive education. Key words: professionalism, teacher-defectologist (assistant child), theory and practiceof correctional and educational work, teacher training.